Understanding the spatial dynamics of values and disvalues in the Kaskaskia River Watershed, USA through a social-ecological lens - Carena J. van Riper; Lorraine Foelske; Ben Leitschuh; Sanghyun Lee; Suresh Sharma; Seunguk Shin; Henry Pollock; Maria L. Chu; William P. Stewart (Ecosystems and People)
Maintaining a resilient and sustainable agro-production system is replete with challenges, because management practices designed to enhance productivity can overlook the range of values derived from ecosystems and concerns about their future. Further complicating the decisions being made about agricultural settings is the variation in social-ecological stressors that shape how diverse community members interpret landscape change. We engaged residents of the Kaskaskia River Watershed in Illinois, USA in discussions about agroecosystems through participatory mapping exercises and focus groups. The spatially explicit data that were derived from this process were then modeled in relation to changes in watershed hydrology simulated using a Soil and Water Assessment Tool (SWAT) model. We observed that the four most salient ‘values’ associated with the watershed were recreation, erosion protection, crop production, and flood control. Erosion, siltation and sedimentation, increased flooding, and invasive species were considered the most relevant ‘disvalues’ because they represented the social-ecological stressors of greatest concern. Respondents believed that the values from ecosystems were more spatially clustered than disvalues, and the main river corridor was at greater risk of degradation than the associated tributaries despite these second order streams being more biologically diverse. The use of participatory mapping data coupled with SWAT to simulate changes in systemic responses of the watershed provided a social-ecological basis for identifying high and low-priority locations at a regional scale. Our results therefore aim to spatial prioritize and guide evidence-based decisions anchored in the social and ecological complexities of a Midwestern watershed.